Early B Cell and Plasma Cell Kinetics Upon Treatment Initiation Portend Flares in Systemic Lupus Erythematosus: A Post-Hoc Analysis of Three Phase III Clinical Trials of Belimumab - Parodis, Ioannis; Gomez, Alvaro; Chow, Jun Weng; Borg, Alexander; Lindblom, Julius; Gatto, Mariele (Frontiers in Immunology, 2022)
Objective To investigate changes in B cell subsets in relation to disease flares upon initiation of standard therapy (ST) plus belimumab or placebo in patients with systemic lupus erythematosus (SLE). Patients and Methods Using data from the BLISS-76, BLISS-SC and BLISS Northeast Asia trials, we investigated associations of relative to baseline rapid (through week 8) and early (through week 24) changes in peripheral B cell subsets, anti-dsDNA and complement levels with the occurrence of disease flares from week 24 through week 52 (Mann-Whitney U tests) or the entire study follow-up (Cox regression analysis), assessed using the SELENA-SLEDAI Flare Index. Results Patients on ST alone who flared displayed less prominent early decreases in CD19+CD20-CD138+ long-lived plasma cells (-16.1% versus -35.1%; P=0.012). In all arms combined, patients who developed severe flares showed less prominent early decreases in CD19+CD20-CD138+ long-lived plasma cells (-23.5% versus -39.4%; P=0.028) and CD19+CD27brightCD38bright SLE-associated plasma cells (-19.0% versus -27.8%; P=0.045). After adjustment for rapid changes, early increases in overall CD19+CD20+ B cells (HR: 1.81; 95% CI: 1.08–3.05; P=0.024) and early increases or no return after a rapid expansion in CD19+CD20+CD27+ memory B cells (HR: 1.58; 95% CI: 1.18–2.11; P=0.002) portended subsequent severe flares. Patients who developed flares of any severity showed no or less prominent rapid (0.0% versus -12.5%; P<0.001) or early (-1.9% versus -21.7%; P<0.001) decreases in anti-dsDNA levels, and patients who developed severe flares showed no or less prominent early decreases in anti-dsDNA levels (0.0% versus -13.3%; P=0.020). Changes in complement levels exhibited no ability to distinguish flaring from non-flaring patients. Conclusions Increase or lack of decrease in certain circulating B cell subsets or anti-dsDNA levels upon treatment initiation for active SLE heralded subsequent severe disease flares. A rapid expansion of memory B cells may signify sustained response to therapy when followed by a subsequent drop, while no return or delayed increases in memory B cells may portend flaring. Peripheral B cell and serological marker kinetics may help identify patients in whom therapeutic modifications could protect against flare development, and may hence prove a useful complement to traditional surveillance and early treatment evaluation in SLE.